Safeguarding in practice: anticipating, minimising and mitigating risk in teenage pregnancy research in urban informal settlements in Nairobi, Kenya - Miriam Taegtmeyer; Linet Okoth; Lilian Otiso; Sally Theobald; Phil Tubb; Penelope A Phillips-Howard; Elizabeth Nyothach; Rosie Steege; Inviolata Njoroge (BMJ Global Health)
Safeguarding challenges in global health research include sexual abuse and exploitation, physical and psychological abuse, financial exploitation and neglect. Intersecting individual identities (such as gender and age) shape vulnerability to risk. Adolescents, who are widely included in sexual and reproductive health research, may be particularly vulnerable. Sensitive topics like teenage pregnancy may lead to multiple risks. We explored potential safeguarding risks and mitigation strategies when studying teenage pregnancies in informal urban settlements in Nairobi, Kenya. Risk mapping was initiated by the research team that had prolonged engagement with adolescent girls and teen mothers. The team mapped potential safeguarding risks for both research participants and research staff due to, and unrelated to, the research activity. Mitigation measures were agreed for each risk. The draft risk map was validated by community members and coresearchers in a workshop. During implementation, safeguarding risks emerged across the risk map areas and are presented as case studies. Risks to the girls included intimate partner violence because of a phone provided by the study; male participants faced potential disclosure of their perceived criminal activity (impregnating teenage girls); and researchers faced psychological and physical risks due to the nature of the research. These cases shed further light on safeguarding as a key priority area for research ethics and implementation. Our experience illustrates the importance of mapping safeguarding risks and strengthening safeguarding measures throughout the research lifecycle. We recommend co-developing and continuously updating a safeguarding map to enhance safety, equity and trust between the participants, community and researchers.